NETWORK OF AFFECTION: EKSPLORASI INTERPERSONAL TRUST, PERCEIVED INTERPERSONAL CLOSENESS, DAN KEPUASAN HUBUNGAN ROMANTIS PADA ONLINE DATERS - Hapsari, Indria; Cahyanti, Indah; Gunawan, Dyah Ayu Kusumawardani; Fachrial, Lia Aulia; Musa, Purnawarman (Jurnal Psikologi, 2024)
The aim of this research is to examine the influence of interpersonal trust and perceived interpersonal closeness on romantic relationship satisfaction in individuals undergoing online dating through one or more applications such as Tinder, Coffee Meets Bagel, as well as social networking applications like Facebook. The sampling technique used is the snowball sampling method with a sample size of 50 adult individuals above 18 years old, consisting of 38 women and 12 men, who had been in an online romantic relationship for at least 1 month. Data analysis uses multiple regression techniques. The research results show that there is an influence of interpersonal trust and perceived interpersonal closeness separately and together on romantic relationship satisfaction in individuals who experience online dating. Analysis of the data together shows an F value coefficient of 26.386 with a significance of 0.001 (ρ ≤ 0.05) and an R square of 0.658. This means that there is a very significant influence between interpersonal trust and perceived interpersonal closeness together on romantic relationship satisfaction in individuals undergoing online dating with a relative contribution of 65.8% while the remaining 34.2% is influenced by other factors not included in this research. The considerable contribution of interpersonal trust and perceived interpersonal closeness occurs because they collectively form the basis of intimacy and effective communication, as well as increasing feelings of emotional connection in the digital realm, thus increasing satisfaction in online dating.